IN SILICO ANALYSIS OF BRUGUIERA GYMNORRHIZA (L.) – LARGE LEAVED MANGROVE FOR EFFICIENT THERAPEUTIC USES - A, ARUNPRASATH; S, SREERAM (Asian Journal of Pharmaceutical and Clinical Research, 2021)
Objective: The study was focused on obtaining the therapeutic advantages of Bruguiera gymnorrhiza, a large leafed mangrove through in silico studies. Methods: The collected leaf sample was extracted using ethanol, and the extract was subjected to GCMS analysis to find out the compounds present in them. The obtained compounds underwent absorption, distribution, metabolism, and elimination toxicity test and the chemical structures were obtained from PUBCHEM and the disease which had more susceptibility was taken on the basis of antimicrobial studies and its protein structure was also obtained from Protein Data Bank. Maestro is a freely available, full future molecular visualization tool. It is a powerful tool for interpreting, managing, and sharing the results of computational experiments when coupled with Schrodinger software such as Glide, Prime, or Phase. The compatibility of ligand-protein interaction was visualized through the visualization software that is Pymol. Results: The retrieved compounds were subjected to analyze the absorption, distribution, metabolism, and excretion properties and the results were tabulated. It was found that the compound 2-Methoxy-4-Vinylphenol; 7786-61-0; 4-Vinylguaiaco from the plant sample B. gymnorrhiza shows a glide score (G. score) −7.2 Kcal/mol. The interactions were observed using Pymol. Conclusion: It was found that the compound 4-Vinylguaiaco from the plant sample B. gymnorrhiza can be used as potent drug for the treatment of pharyngitis, which is the inflammation of pharynx. This work can be taken as a base for the works that need to be done in future for the development of an effective drug and also addressing the importance of mangroves in the field of ethnobotany.